2018
DOI: 10.3194/1935-8156-13.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Excel: Software Tools and the Accounting Curriculum

Abstract: The ability to use various software and tools is important for students entering the accounting profession. In an exploratory study, we develop a survey to assess accounting practitioners' evaluations of the importance of various software tools, as well as the importance of data analytics and data visualization skills. Responses from 197 practitioners indicate that Excel is the most frequently utilized software / tool, the most important software tool for new hires, and that Excel should be emphasized in unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 11 publications
3
33
0
1
Order By: Relevance
“…This study, like previous research, finds that three IT skills continue to be in the top five rankings regardless of whether or not firm size is a consideration:  spreadsheets (Dillon & Kruck, 2008;Chen et al, 2009;Welch et al, 2010;Cory & Pruske, 2012;Kearns, 2014;Lee et al, 2018)  Word Processing (Chen et al, 2009;Welch et al, 2010;Cory & Pruske, 2012)  Internet research (Welch et al, 2010;Cory & Pruske, 2012). This research's results also support previous findings that firm size is not a factor for Cloud Computing (Gupta et al, 2013;Seethamraju, 2015;Loukis et al, 2017).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This study, like previous research, finds that three IT skills continue to be in the top five rankings regardless of whether or not firm size is a consideration:  spreadsheets (Dillon & Kruck, 2008;Chen et al, 2009;Welch et al, 2010;Cory & Pruske, 2012;Kearns, 2014;Lee et al, 2018)  Word Processing (Chen et al, 2009;Welch et al, 2010;Cory & Pruske, 2012)  Internet research (Welch et al, 2010;Cory & Pruske, 2012). This research's results also support previous findings that firm size is not a factor for Cloud Computing (Gupta et al, 2013;Seethamraju, 2015;Loukis et al, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…Much of the employer needs research relies on surveys of Certified Public Accountants (CPAs) primarily in large public accounting firms. Lee, Kerler, and Ivancevich (2018) indicate their respondents are CPAs in "public accounting since it represents entry-level job placement for many graduates of Accounting Master's programs" (p. 47). The majority of undergraduate accounting students, however, do not go into, or do not stay in, large public accounting firms and addressing their needs is important when identifying topics for an undergraduate AIS course (Schea, 2008;Siegel, Sorensen, Klammer, & Richtermeyer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the many auditing software available in the market, general spreadsheet software Microsoft Excel continues to show its dominance. Literature indicates that auditors use Excel very frequently on their daily working activities [11,13,16,17,18,19,20]. The dominance of Excel is not limited to public accounting, Excel has been used across different accounting areas [18], such as in managerial accounting [21,22], financial reporting [23,24], and public accounting sector [11,13,17,18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the perspective of accounting faculty, Rackliffe and Ragland (2016) explore Excel in the accounting curriculum and find that faculty understand the importance of Excel in public accounting and the need to improve students' overall proficiency in Excel. Finally, in an exploratory study, Lee, Kerler, and Ivancevich (2018) identified Excel as the most frequently utilized software or tool used by accounting practitioners, as well as the most important software tool for new hires.…”
Section: Excelmentioning
confidence: 99%